Regulation of Cl(−)(in) signaling and ion transport by IRBIT-mediated recruitment of multiple kinases and phosphatases - Vachel, Laura (Sci Signal, 2018)
IRBIT is a multifunctional protein that controls the activity of IP(3) receptors and the Cl(−) and HCO(3)(−) transporters NBCe1-B, CFTR and Slc26a6, by an unknown mechanism. IRBIT interacts with the NBCe1-B N terminus autoinhibitory domain (AID), exposing two cryptic Cl(−) sensing GXXXP sites to confer regulation of NBCe1-B by Cl(−)(in). Here, LC-MS/MS phosphoprotein analysis revealed that IRBIT controls five NBCe1-B phosphorylation sites that determine both NBCe1-B active conformations and regulation by Cl(−)(in). Specifically, IRBIT-dependent combinatorial dephosphorylation of pS(232), pS(233) or pS(235) generated the conformations pS(233)/pS(235), pS(232)/pS(235) or pS(232)/pS(233). The pS(233)/pS(235) conformer was fully active, and was no longer activated by IRBIT or inhibited by Cl(−)(in). The pS(232)/pS(235) conformer properties were similar to those of wild-type NBCe1-B, while the pS(232)/pS(233) conformer was partially active, had higher affinity for IRBIT, but retained inhibition by Cl(−)(in). In addition, IRBIT recruited the phosphatase PP1 and the kinase SPAK to control S(65) phosphorylation, which reciprocally affected Cl(−)(in) sensing by the (32)GXXXP(36) motif. IRBIT recruited the phosphatase calcineurin and the kinase CaMKII to control phosphorylation of S(12), which reciprocally affected Cl(−)(in) sensing by the (194)GXXXP(198) motif. S(232)/S(233)/S(235) are conserved in several NBC transporters. Mutating the serines to alanines resulted in fully active transporters, while mutating the serines to the phosphormimetic aspartates resulted in inhibited transporters, suggesting that S(232)/S(233)/S(235) determine whether NBC transporters are in active or inactive conformations. These findings reveal how multiple kinase/phosphatase pathways use multiple phosphorylation sites to fine tune a transport function, which have important implications for epithelial fluid and HCO(3)(−) secretion.